1994
DOI: 10.1093/jpepsy/19.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Hemophilia Growth and Development Study: Baseline Neurodevelopmental Findings

Abstract: Reported baseline findings from the neurological assessment component of the Hemophilia Growth and Development Study (HGDS). HIV-positive (HIV+; n = 207) and HIV-negative (HIV-; n = 126) young males with hemophilia ages 6 to 18 years, were enrolled in a prospective study of their growth and development. At baseline, HIV+ and HIV- subjects were not significantly different in test performance. The number of subjects exhibiting below-average performance in three or more areas assessed was about 25% overall. For b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 0 publications
5
42
0
Order By: Relevance
“…Higher school absenteeism rates compared with their nonaffected classmates 6,9 and lower academic performance relative to potential have also been documented. 10 The primary occupation of young children is preparation for and participation at school. Factors that interfere with completion of these important tasks can result in the inability of the child to fulfill his or her potential during school and later in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher school absenteeism rates compared with their nonaffected classmates 6,9 and lower academic performance relative to potential have also been documented. 10 The primary occupation of young children is preparation for and participation at school. Factors that interfere with completion of these important tasks can result in the inability of the child to fulfill his or her potential during school and later in life.…”
Section: Discussionmentioning
confidence: 99%
“…5 Several reports in the literature document higher rates of school absenteeism in children with hemophilia than in others 6 -9 and discrepancies between children's potential and achievement as they progress through the upper grades. 8 Studying children enrolled in the multicenter Hemophilia Growth and Development Study (HGDS), Loveland et al 10 reported lower achievement than expected based on IQ at the baseline examination. Analyses of baseline and longitudinally collected HGDS data demonstrated associations between the functional severity of hemophilia, measured by abnormalities in coordination and gait, and academic performance.…”
Section: Vs 413)mentioning
confidence: 99%
“…1,27,29 -33 However, Cohen et al 34 did not find significant differences between HIV-infected and noninfected children in global intellectual ability, even 4 1 ⁄2 to 8 1 ⁄2 years after onset, and others [35][36][37] have noted that neuropsychological profiles in HIV-infected and noninfected hemophiliacs did not differ. Thus, infants and children infected with HIV infection have, sometimes, but not always, been found to have deficits in global intellectual functioning.…”
mentioning
confidence: 95%
“…Similarly, abnormalities on neuroimaging were limited to the same group [Mitchell et al, 1993]. Seropositive subjects did not differ on most aspects of neuropsychological testing from seronegative subjects [Loveland et al, 1994]. Longitudinal followup of the group revealed that behavioral changes and diffuse muscle atrophy were the only significant neurological findings attributable to HIV, and only very late in the course, usually in the six months preceding death [Mitchell et al, 1997].…”
Section: Cognitive Functioning Of Older Children With Hiv Infection Amentioning
confidence: 97%